2019
DOI: 10.22159/ajpcr.2019.v12i3.29085
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening, Antimicrobial, and Antioxidant Activities of Root and Leaf Extracts of Leucas Aspera

Abstract: Objective: The present study was designed to evaluate the phytochemical screening, antimicrobial, and antioxidant activities from the roots and leaves of Leucas aspera. Methods: The phytochemical screening and Fourier transform infrared (FTIR) analysis of root and leaf extracts were studied using standard methods. The disk diffusion method was performed to analyze the antimicrobial activity of aqueous extract, methanol extract and hexane extract of root and leaf against to selected bacterial and fungal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…D*-extract also possessed concentrated biological important phytochemicals such as polyphenols and flavonoids. Kumar, Nehra [60] showed that E. faecalis is most sensitive to plant compounds such as polyphenols. Therefore, this specific strain (as compared to other strains) in our study showed increased sensitivity to H-extract, D-extract, and D*-extract.…”
Section: Plos Onementioning
confidence: 99%
“…D*-extract also possessed concentrated biological important phytochemicals such as polyphenols and flavonoids. Kumar, Nehra [60] showed that E. faecalis is most sensitive to plant compounds such as polyphenols. Therefore, this specific strain (as compared to other strains) in our study showed increased sensitivity to H-extract, D-extract, and D*-extract.…”
Section: Plos Onementioning
confidence: 99%